2021
DOI: 10.1002/mas.21745
|View full text |Cite
|
Sign up to set email alerts
|

Gas‐phase structure of polymer ions: Tying together theoretical approaches and ion mobility spectrometry

Abstract: An increasing number of studies take advantage of ion mobility spectrometry (IMS) coupled to mass spectrometry (IMS-MS) to investigate the spatial structure of gaseous ions. Synthetic polymers occupy a unique place in the field of IMS-MS.Indeed, due to their intrinsic dispersity, they offer a broad range of homologous ions with different lengths. To help rationalize experimental data, various theoretical approaches have been described. First, the study of trend lines is proposed to derive physicochemical and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 170 publications
0
3
0
Order By: Relevance
“…progress in MS, as a highly and sensitive detector, is also required. Current MS often equips a functionality of ion mobility spectrometry (IMS), a type of electrophoretic separation in the gaseous phase, and IMS-MS have been applied to various research field [62][63][64][65][66][67][68][69][70][71]. A combination of HPLC with IMS-MS(/MS) is also significant as a kind of multi-dimensional separation.…”
Section: Discussionmentioning
confidence: 99%
“…progress in MS, as a highly and sensitive detector, is also required. Current MS often equips a functionality of ion mobility spectrometry (IMS), a type of electrophoretic separation in the gaseous phase, and IMS-MS have been applied to various research field [62][63][64][65][66][67][68][69][70][71]. A combination of HPLC with IMS-MS(/MS) is also significant as a kind of multi-dimensional separation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these experimental results, molecular modeling is often used to determine the theoretical Ω value of each potential architecture. Comparison of the theoretical and experimental Ω values allows for a confident structural assignment of polymer architecture, protein folding, and molecular packing arrangement [ 33 , 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, ion mobility spectrometry (IMS) experiments represent an invaluable analytical method to generate structural data on gas-phase ions . By comparing the measured collision cross sections (CCS) with theoretical CCS obtained on candidate ion structures generated upon MD simulations, description of the gas phase ion structures may be afforded at the molecular level. , The IMS/MD combination requires that the MD parameters and the IMS calibration are adequately set up, and elegant studies on protein ions, synthetic polymers and dendrimers , are reported.…”
Section: Introductionmentioning
confidence: 99%
“…21 By comparing the measured collision cross sections (CCS) with theoretical CCS obtained on candidate ion structures generated upon MD simulations, description of the gas phase ion structures may be afforded at the molecular level. 21,22 The IMS/MD combination requires that the MD parameters and the IMS calibration are adequately set up, and elegant studies on protein ions, 23 synthetic polymers 24 and dendrimers 25,26 are reported. However, Gabelica et al demonstrated that gaseous DNA ions are often characterized by more compact structures than in solution, which are not reproduced using MD simulations when the starting point is the fully desolvated canonical double-helix conformation.…”
Section: ■ Introductionmentioning
confidence: 99%